Lower plasma PCSK9 in normocholesterolemic subjects is associated with upregulated adipose tissue surface‐expression of LDLR and CD36 and NLRP3 inflammasome. Issue 3 (1st February 2021) - Cyr, Yannick; Lamantia, Valérie; Bissonnette, Simon; Burnette, Melanie; Besse‐Patin, Aurèle; Demers, Annie; Wabitsch, Martin; Chrétien, Michel; Mayer, Gaétan; Estall, Jennifer L.; Saleh, Maya; Faraj, May
Abstract: Background: LDL‐cholesterol lowering variants that upregulate receptor uptake of LDL, such as in PCSK9 and HMGCR, are associated with diabetes via unclear mechanisms. Activation of the NLRP3 inflammasome/interleukin‐1 beta (IL‐1β) pathway promotes white adipose tissue (WAT) dysfunction and type 2 diabetes (T2D) and is regulated by LDL receptors (LDLR and CD36). We hypothesized that: (a) normocholesterolemic subjects with lower plasma PCSK9, identifying those with higher WAT surface‐expression of LDLR and CD36, have higher activation of WAT NLRP3 inflammasome and T2D risk factors, and; (b) LDL upregulate adipocyte NLRP3 inflammasome and inhibit adipocyte function. Methodology: Post hoc analysis was conducted in 27 overweight/ obese subjects with normal plasma LDL‐C and measures of disposition index (DI during Botnia clamps) and postprandial fat metabolism. WAT was assessed for surface‐expression of LDLR and CD36 (immunohistochemistry), protein expression (immunoblot), IL‐1β secretion (AlphaLISA), and function ( 3 H‐triolein storage). Results: Compared to subjects with higher than median plasma PCSK9, subjects with lower PCSK9 had higher WAT surface‐expression of LDLR (+81%) and CD36 (+36%), WAT IL‐1β secretion (+284%), plasma IL‐1 receptor‐antagonist (+85%), and postprandial hypertriglyceridemia, and lower WAT pro‐IL‐1β protein (−66%), WAT function (−62%), and DI (−28%), without group‐differences in body composition, energy intake or expenditure. Adjusting for WAT LDLR or CD36 eliminated group‐differences in WAT function, DI, and postprandial hypertriglyceridemia. Native LDL inhibited Simpson‐Golabi Behmel‐syndrome (SGBS) adipocyte differentiation and function and increased inflammation. Conclusion: Normocholesterolemic subjects with lower plasma PCSK9 and higher WAT surface‐expression of LDLR and CD36 have higher WAT NLRP3 inflammasome activation and T2D risk factors. This may be due to LDL‐induced inhibition of adipocyte function.